Seroprevalence rates of hepatitis c virus (hcv) antibody and hepatitis b virus surface antigen (hbsag) in blood donors in a southwestern nigerian city (2014)
Hepatitis B and C have been identified as major causes of Transfusion transmitted infections, in Nigeria. Our objective was to determine the prevalence of Hepatitis B virus (HBV) and Hepatitis C virus (HCV) in prospective blood donors in Abeokuta, Nigeria. 305 blood donors were screened for the presence of Hepatitis B virus surface antigen (HBsAg) and HCV using a rapid immunochromatographic kit (DiaSpot®). Demographic information was also collected. Males constituted 96.4%, singles were the majority with 65%. Prevalence of HBsAg was 9.8%, HCV 1.3%, and dual positivity 0.3%. Prevalence of HBsAg and HCV among males was 10.2% and 1.4%, while females recorded 0.0% for HCV and HBsAg. Dual positivity was recorded in a male (0.33%). Analysis of the study variables revealed that only educational status was statistically associated with positivity of HBsAg (χ2 = 7.49, p = 0.02), HCV prevalence was highest in the illiterate group it was not statistically significant (P > 0.05). We report the prevalence rates of anti-HCV Ab and HBsAg in blood donors from Ogun State, Nigeria. Our results reveals higher rate of HBsAg and evidence of co-infection with both viruses, illiteracy was the only variable associated with HBV infection. We advocate for the inclusion of anti-HBc or HBeAg in donor screening in our environment.